Novice Voters Politics Culture (The Study About the Orientation of Novice Voters Politics on the Election of the Mayor and Vice Mayor in Kendari in Year 2017) - BAHTIAR, Unhalu (Journal of Advanced Research in Law and Economics, 2017)
Democracy is important for every people, in order to create democratic country. The voter is an important part of democracy. Simply election is the way of citizen to do politics activity or politics contract with another person or politics party who are given the mandate or the authority to implement the partly power of people/voters. This study was conducted with the aim to study about the orientation of novice voters politics on the election of the mayor and vice mayor in Kendari in year 2017. The informant of the research was individual who would use his election rights for the first time in direct election. Structural model presented the relationship among study variables. Coefficient of structural model stated the magnitude relationship between one variable to another variable. Based on the analysis results, it can be concluded that factors that affect novice voters in using their election rights in the election of Mayor and Vice Mayor of Kendari in 2017 are factor that influence older people, factor of individual’s choice, factor of mass media, politics party and politics advertisement and contemporary friend.